A New Collection Tool-Kit to Sample Microplastics From the Marine Environment (Sediment, Seawater, and Biota) Using Citizen Science - Paradinas, Lola M.; James, Neil A.; Quinn, Brian; Dale, Andrew; Narayanaswamy, Bhavani E. (Frontiers in Marine Science, 2021)
Microplastics (plastic particles ≤5 mm) have been studied extensively in coastal areas around the world in several habitats. Nevertheless, understanding and explaining the temporal and spatial occurrence and dynamics of microplastics is challenging. For the first time, three environmental variables were studied at six locations at the same time for each season over a year, along the North and West coasts of Scotland. Surface water was collected with a pole water sampler from the shore whilst beach sediment was sampled using glass jars, and mussels were the target organism collected. Concentrations of microplastics ranged from 0 to 6 ± 1.50 particles per l of surface water. In beach sediment, microplastics concentrations ranged from 0 to 0.37 ± 0.12 particles per g.dw, whilst for mussels it ranged from 0 to 23.81 particles per g.ww. This study was designed to determine the presence of microplastics as well as extend the temporal and geographical scales. We developed a simple, cost-effective and practical tool-kit to collect microplastics from the coastal environment and engaged the public in scientific research. The tool-kit was designed to take into account the latest recommendations for sampling each environmental substrate, whilst being practical for citizen scientists to use. This research demonstrates that using a semi-structured to structured project with a defined sampling approach including the participation of the public with local knowledge can be an effective way to monitor microplastics in the marine environment along the Scottish coastline. This approach can be adapted to other projects monitoring microplastics to increase the use of citizen science in projects, allowing more studies to take place, more samples to be collected, and a greater understanding of the occurrence and the potential impact of microplastics in the environment.